2011
DOI: 10.1186/1471-2393-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Identifying postpartum intervention approaches to prevent type 2 diabetes in women with a history of gestational diabetes

Abstract: BackgroundWomen who develop gestational diabetes mellitus (GDM) have an increased risk for the development of type 2 diabetes. Despite this "window of opportunity," few intervention studies have targeted postpartum women with a history of GDM. We sought perspectives of women with a history of GDM to identify a) barriers and facilitators to healthy lifestyle changes postpartum, and b) specific intervention approaches that would facilitate participation in a postpartum lifestyle intervention program.MethodsWe us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
209
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(218 citation statements)
references
References 26 publications
7
209
0
2
Order By: Relevance
“…In one of the related studies, most participants changed their life style based on information available on the Internet. The authors suggested the low cost of acquiring information via the Internet and the difficulties of attending classes and receiving face-toface training, as the causes of inclination towards the use of the Internet as an information source (23). All these studies are somehow consistent with the present study and reflect the strong role of training in creating motivation for self-care and for making lifestyle changes.…”
Section: Resultssupporting
confidence: 80%
“…In one of the related studies, most participants changed their life style based on information available on the Internet. The authors suggested the low cost of acquiring information via the Internet and the difficulties of attending classes and receiving face-toface training, as the causes of inclination towards the use of the Internet as an information source (23). All these studies are somehow consistent with the present study and reflect the strong role of training in creating motivation for self-care and for making lifestyle changes.…”
Section: Resultssupporting
confidence: 80%
“…It has been shown, for example, that only 16% of women with previous GDM believed themselves to be at high risk for T2D, and women with greater perceptions of risk intended more often to change their lifestyle in a healthier direction. 19 Common barriers to lifestyle changes in women with GDM have been child care duties, fatigue, work-related obstacles, and lack of time and motivation 18 and-for example, in a behavioral intervention study among women with GDM-an increase in physical activity targets was not attained. 14 Our result of the effect of lifestyle intervention on the incidence of T2D between women with and without GDM is in line with the results of the DPP trial.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot analyze in detail the true effectiveness of our intervention due to the lack of counselling data collected. We suggest that novel approaches, such as Internet-based lifestyle interventions, 18 may also be useful in order to benefit more from lifestyle interventions in women with GDM. An interesting finding was also that a high number of women at risk did not participate in the program at all after the baseline, reflecting the situation ''in real life.''…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, there was controversy about the relationship between using insulin in GDM and doing the screening. Some studies reported a positive relationship between insulin use in GDM and screening (15,21). Another study reported a negative relationship (22), and some studies reported no relationship (19,23).…”
Section: Discussionmentioning
confidence: 98%